Percutaneous versus surgical femoral access in minimally invasive cardiac operations. (20th April 2022) - El-Sayed Ahmad, Ali; Bayram, Ali; Salamate, Saad; Sirat, Sami; Amer, Mohamed; Bakhtiary, Farhad
Abstract: OBJECTIVES: Both surgical and percutaneous femoral accesses for the establishment of extracorporeal circulation are used in minimally invasive cardiac surgeries. The goal of this study was to compare the outcomes with the MANTA vascular closure device after percutaneous arterial decannulation via the surgical approach. METHODS: Between November 2018 and January 2021, a total of 490 consecutive patients underwent minimally invasive cardiac operations at our institution. Cannulation and decannulation of femoral vessels were under direct vision surgically or percutaneously. The MANTA system was used to close the femoral artery in all patients with percutaneous cannulation. Demographic, clinical and procedural data were collected retrospectively. RESULTS: Surgical cut-down and suture closure of the femoral artery was performed in 222 patients (45.3%); percutaneous access and closure with the MANTA system was used in 268 patients (54.7%). The surgical group presented a significantly higher incidence of any access site complication compared to the percutaneous group [18 patients (8.1%) vs 6 patients (2.2%); P  =   0.003]. Lymph fistula and wound healing disorders occurred more frequently in the surgical group (3.2% vs 0% [ P  =   0.004] and 3.6% vs 0% [ P  =   0.002], respectively). Median procedural duration and stays in the intensive care unit were significantly lower in the percutaneous group {127 [interquartile range (IQR) 97–158] min vs 150 (IQR 117–185) min ( P  <   0.001) and 1 (IQR 1–2) day vs 2 (IQR 1–3) days ( P  =   0.008), respectively}. CONCLUSIONS: Percutaneous access and closure with the MANTA system are feasible, safe and associated with lower incidences of all-cause access site complications and shorter stays in the intensive care unit compared to surgical access and closure in minimally invasive cardiac surgeries. Abstract : In the last few decades, cardiovascular surgery has gradually shifted towards a minimally invasive approach for various procedures such as valve procedures, coronary artery bypass and intracardiac tumour resection.